Fracture characterization of a cast aluminum alloy aiming machining simulation. (March 2019) - Silva, TEF; Gain, S; Pinto, D; de Jesus, AMP; Xavier, J; Reis, A; Rosa, PAR
Despite extensive research regarding metal cutting simulation, the current industrial practice very often relies on empirical data when it comes to tool design. In order accurately simulate the cutting process it is not only important to have robust numerical models that closely portray the phenomenon, but also to properly characterize the material taking into account the cutting conditions. The goal of this investigation focuses on the mechanical characterization of the cast aluminum alloy AlSi9 Cu3 by conducting both compression and fracture tests. Due to its very good castability, machinability, and attractive mechanical properties, this alloy is widely used in casting industry for the manufacture of automotive components, among others. Besides the experimental characterization, a numerical methodology is proposed for the modeling of the cast alloy, making use of the Johnson–Cook constitutive material model, in Abaqus/CAE. The material model is calibrated based on compression tests at multiple conditions (quasi-static, incremental dynamic and high temperatures). The identified model is then validated by simulation of the ductile fracture tests of notched specimens. The obtained numerical results were consistent with the experimentally obtained, contributing to the validity of the presented characterization technique.